THE INFLUENCE OF INNOVATION ON TOURISM ATTRACTIVENESS IN SELECTED LOCATIONS IN THE SUDETY MOUNTAINS - Daria Jaremen; Piotr Gryszel; Andrzej Rapacz (Acta Scientiarum Polonorum. Oeconomia, 2010)
Tourism constitutes and may become a significant factor infl uencing regional economic development, although it does not represent a phenomenon unchangeable in time. Contemporary tourist turns out a more and more demanding consumer who expects an offer catering for his/her individual needs and expectations. Growing mobility and an increasing level of income in the society result in tourism oriented trips becoming more and more popular. Frequent travelling provides an opportunity for tourists to compare offers they obtain. Requirements also grow regarding the quality and standard of supplied services. Contemporary tourists search for new offers which are not standard ones, but are characterized by a unique profile. A similar situation occurs in case of overall tourism offer supply, since there occurs a growing competition between tourism enterprises and regions. They take the utmost care in order for their locations and enterprises to upgrade their attractiveness as observed by potential tourists and clients. The presented paper illustrates activities of entrepreneurs and local authorities of Karpacz, Szklarska Poręba and Świeradów- -Zdrój focused on upgrading tourism attractiveness by undertaking innovation activities.